2005
DOI: 10.1021/jo050872p
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the C3-Symmetry of Chiral Tripodal Oxazolines:  Enantio-Discrimination of Chiral Organoammonium Ions

Abstract: [structure: see text] A phenylglycinol-derived tripodal oxazoline with C1-symmetry (C1-PhBTO) was synthesized, and its enantioselective recognition behavior toward alpha-chiral primary organoammonium ions was studied. The C1-PhBTO receptor showed higher selectivity with an opposite sense of enantio-discrimination compared to other C1-symmetric analogues examined but lower selectivity with the same sense of enantioselection compared to its C3-symmetric analogue. Binding studies indicated that the C1-symmetric r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Theoretical studies indicated such trisoxazolines are alternatives to azacrowns for binding and sensing of ammonium and alkylammonium ions [565567]. The importance of the C 3 symmetry in chiral recognition has been pointed out [555].…”
Section: Reviewmentioning
confidence: 99%
“…Theoretical studies indicated such trisoxazolines are alternatives to azacrowns for binding and sensing of ammonium and alkylammonium ions [565567]. The importance of the C 3 symmetry in chiral recognition has been pointed out [555].…”
Section: Reviewmentioning
confidence: 99%
“…It may certainly be the case that the energy difference between the host–guest complexes of enantiomeric ammonium ions with a host with lower symmetry ( C 1 or C 2 ) is larger, but there is no fundamental rule governing these differences. To further study the role of symmetry, Ahn and co‐workers recently prepared a receptor, 4 , with reduced symmetry in which one of the substituents was replaced by one with opposite chirality 8. This led to lower selectivity but also to a different type of binding (2:1 host–guest complex) owing to the different structures of the ligands.…”
mentioning
confidence: 99%
“…Removing the β-OH group from 225, as in 226 or 227, (Figure 22) results in low enantioselectivities, hence indicating that the secondary H-bond interaction is critical to secure the necessary environment for chiral discrimination as confirmed by the crystallographic structure of the corresponding 215-225 complex. In the next article [93] the development of a benzene-based tripodal oxazoline receptor with C1-symmetry, 234 upon changing the symmetry of chiral environment from C3 to C1 was reported (Scheme 38). The synthetic strategy was based on the coupling of tris-(cyanomethyl)mesitylene with (S)-phenylglycinol in the presence of 5 mol % Cd(OAc)2 to furnish (S,S)-bis(oxazoline), 233 and subsequent treatment with (R)-phenylglycinol under the similar reaction conditions afforded (S,S,R)-234 in 28% isolated yield.…”
Section: Chartmentioning
confidence: 99%
“…In the next article [93] the development of a benzene-based tripodal oxazoline receptor with C1-symmetry, 234 upon changing the symmetry of chiral environment from C3 to C1 was reported (Scheme 38). The synthetic strategy was based on the coupling of tris-(cyanomethyl)mesitylene with (S)-phenylglycinol in the presence of 5 mol % Cd(OAc)2 to furnish (S,S)-bis(oxazoline), 233 and subsequent treatment with (R)-phenylglycinol under the similar reaction conditions afforded (S,S,R)-234 in 28% isolated yield.…”
Section: Entrymentioning
confidence: 99%